a Nusyuz Suami Serta Mekanisme Penyelesaiannya Perspektif Fikih Munakahat - Nasrulloh, Muhammad; Ubaid Ermawan, Mohamad Zakky (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2024)
Nusyūz was often associated with women. This stereotype has led to a legal gap, where it is perceived that only women are bound by nusyūz, while men are unfamiliar with the term. In fact, the definition of nusyūz can be applied to both men and women. Therefore, this paper aims to recontextualize the term nusyūz to ensure its implementation in a similar manner. The research method used was qualitative, with a library research approach, focusing on fiqh munākaḥāt (Islamic family law). This study was descriptive in nature. The results of the research conclude that nusyūz has two meanings: (1) the decline in the husband's interest and (2) the neglect of rights. The solution to nusyūz in the context of declining interest is reconciliation (iṣlāh). Meanwhile, nusyūz, in the context of neglecting rights, can include neglect of maintenance (nafkah) and domestic violence. The solution is to report the matter to a judge, which could even lead to divorce. Additionally, nusyūz can occur simultaneously in both the partners. The solution in this case involves two negotiators (ḥakam) representing each spouse to make a decision that is beneficial for both parties.